Efficacy and safety of acupoint catgut-embedding for ulcerative colitis: A protocol for systematic review and meta-analysis. Issue 42 (16th October 2020) - Chen, Mingsheng; Xin, Ping; Feng, Kaidi; Zhao, Tianyu; Yang, Xiangdong
Abstract: Background: Ulcerative colitis (UC) is a refractory intestinal disease prone to recurrent attacks, with a high rate of canceration, which seriously affects life treatment. Routine treatment has disadvantages such as long course of treatment, high cost, easy recurrence and limited effectiveness. Clinical practice shows that acupoint catgut embedding therapy has certain therapeutic advantages but lacks evidence of evidence-based medicine. The purpose of this study is to systematically study the effectiveness and safety of acupoint catgut embedding for ulcerative colitis. Methods: Retrieve English database (PubMed, Embase, Web of Science, the Cochrane Library) and Chinese database (CNKI, CDDB, CQVIP, CBM) by computer, and manually retrieve Baidu and Google Academy for randomized controlled trials (RCTs) of acupoint catgut embedding therapy for ulcerative colitis from the time of construction of database to September 2020. Two researchers independently extracted data and evaluated the quality of the literature included in the study, and used RevMan 5.3 software for meta-analysis of the included literature. Result: The study evaluated the effectiveness and safety of acupoint catgut embedding for ulcerative colitis through efficiency, symptom score, colonoscopy score, mucosal healing rate, recurrence rate, incidence of adverse reactions, etc. Conclusion: This study will provide reliable evidence-based evidence for clinical application of acupoint catgut embedding therapy for ulcerative colitis. OSF Registration number: DOI 10.17605/ OSF.IO / 7T4QV.